Perencanaan Pengiriman Mandiri pada Industri Hilir Teh Walini berdasarkan Bangkitan Pergerakan, Sebaran Pergerakan dan Biaya Operasional Kendaraan - Khofifah Nurazizah; Juang Akbardin; Dwi Novi Wulansari (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study is motivated by the downstream Teh Walini industry’s reliance on third-party logistics (3PL) services for product distribution, which restricts the company’s control over several key aspects, including logistics costs, delivery speed, routing efficiency, and product handling quality. The primary objective of this research is to analyze and compare distribution costs between outsourced logistics and self-managed delivery, and to evaluate the potential cost efficiency of an independently operated shipping system. A descriptive comparative quantitative method is employed, incorporating movement generation analysis, distribution spread mapping, and Vehicle Operating Cost (VOC) calculations to estimate the cost implications of self-shipping. Data were obtained through company documentation and analyzed using multiple linear regression involving six major distribution points. The results reveal that shipment volume significantly influences movement generation, with Waingapu, Makassar, and Padang identified as the dominant distribution destinations. The cost comparison analysis demonstrates that self-managed delivery is more cost-effective than third-party logistics services, making it a more viable long-term option. These findings suggest that transitioning to a self-delivery system could improve cost control and logistical efficiency for the company. However, this strategy should be implemented gradually, supported by regular updates on operational cost data and proactive management of external factors that could impact distribution performance. The study concludes by recommending broader coverage and the inclusion of additional relevant variables in future research to further validate and enhance decision-making related to distribution strategies. A well-informed shift toward internal logistics could ultimately contribute to greater competitiveness and sustainability in the company’s distribution operations